Leaf traits variation during leaf expansion in Quercus ilex L. - Gratani, L; Bonito, A (Photosynthetica, 2009)
The morphological, anatomical and physiological variations of leaf traits were analysed during Quercus ilex L. leaf expansion. The leaf water content (LWC), leaf area relative growth rate (RGRl ) and leaf dry mass relative growth rate (RGRm) were the highest (76±2 %, 0.413 cm 2 cm –2 d –1 , 0.709 mg mg –1 d –1 , respectively) at the beginning of the leaf expansion process (7 days after bud break). Leaf expansion lasted 84±2 days when air temperature ranged from 13.3±0.8 to 27.6±0.9 °C. The net photosynthetic rate (PN), stomatal conductance (gs ), and chlorophyll content per fresh mass (Chl) increased during leaf expansion, having the highest values [12.62±1.64 µmol (CO2) m –2 s –1 , 0.090 mol (H2O) m –2 s –1 , and 1.03±0.08 mg g –1 ,respectively] 56 days after bud break. Chl was directly correlated with leaf dry mass (DM) and PN. The thickness of palisade parenchyma contributed to the total leaf thickness (263.1±1.5 μm) by 47 %, spongy layer thickness 38 %, adaxial epidermis and cuticle thickness 9 %, and abaxial epidermis and cuticle thickness 6 %. Variation in leaf size during leaf expansion might be attributed to a combination of cells density and length, and it is confirmed by the significant (p<0.001) correlations among these traits. Q. ilex leaves reached 90 % of their definitive structure before the most severe drought period (beginning of June – end of August). The high leaf mass area (LMA, 15.1±0.6 mg cm –2 ) at full leaf expansion was indicative of compact leaves (2028±100 cells mm –2 ). Air temperature increasing might shorten the favourable period for leaf expansion, thus changing the final amount of biomass per unit leaf area of Q. ilex.
Keywords: leaf anatomy; leaf expansion; leaf morphology; net photosynthetic rate; Quercus ilex

Leaf anatomy, inclination, and gas exchange relationships in evergreen sclerophyllous and drought semideciduous shrub species - Gratani, L; Bombelli, A (PHOTOSYNTHETICA, 1999)
There are significant differences in leaf life-span among evergreen sclerophyllous species and drought semideciduous species growing in the Mediterranean maquis. Cistus incanus, which has a leaf life-span of four-eight months, was characterised by the highest net photosynthetic rates (PN). while Quercus ilex and Phillyrea latifolia, which maintain their leaves two-three and two-four years, respectively, had a lower PN- The longer leaf life-span of the two evergreen sclerophyllous species may be justified to cover the high production costs of leaf protective structures such as cuticle, hairs, and sclereids: cuticle and hairs screen radiation penetrating into the more sensitive tissues, and sclereids have a light-guiding function. Q. ilex and P. latifolia have the highest leaf mass/area ratio (LMA = 209 g m(-2)) and a mesophyll leaf density (2065 cells per mm(2) of leaf cross section area) about two times higher than C. incanus. In the typical evergreen sclerophyllous species the steepest leaf inclination (alpha = 56 degrees) reduces 42% of radiation absorption, resulting in a reduced physiological stress at leaf level, particularly in summer. C. incanus, because of its low leaf life-span, requires a lower leaf investment in leaf protective structures. It exhibits a drastic reduction of winter leaves just before summer drought, replacing them with smaller folded leaves. The lower leaf inclination (alpha = 44 degrees) and the lower LMA (119 g m(-2)) of C. incanus complement photosynthetic performance. Water use efficiency (WUE) showed the same trend in Q. ilex, P. latifolia, and C. incanus, decreasing 60% from spring to summer, due to the combined effects of decreased CO2 uptake and increased transpirational water loss.
Keywords: cistus incanus; leaf inclination; leaf life-span; leaf mass/area ratio; leaf thickness; net photosynthetic rate; phillyrea latifolia; Quercus ilex; transpiration rate

Relationship between photosynthetic activity and chlorophyll content in an isolated Quercus ilex L. tree during the year - Gratani, L; Pesoli, P; Crescente, M F (Photosynthetica, 1998)
The relationship between chlorophyll (Chl) content and net photosynthetic rate (PN) in an isolated Quercus ilex tree, growing inside Villa Pamphili Park in Rome, was explored. The highest Pn was in March, May and September (10.1 umol.m-2.s-1, maximum rate). Pn decreased by 65% (with respect to the yearly maximum) when leaf temperature reached 34ºC, and by 50% when leaf temperature was 9ºC. The highest Chl contents were in April, October [1.47g.kg-1 (d.m.), maximum value], and December. The lowest Chl content was found in July (0.78 g.kg-1). The decrease of PN in July was in close connection with the decrease of Chl content. On the contrary, the high Chl content during winter did not correspond with PN of this season. Discordances between Chl content and PN over the year influenced the regression analysis, which although positive did not show very high correlation coefficients (r=0.79. The high Chl (a+b) content during most of the year indicated that the photosynthetic apparatus remained basically intact also during stress periods.
Keywords: net photosynthetic rate; oak; Regression Analysis; seasonal course; Stomatal conductance